Quantum Gravity in the First Half of the Twentieth Century: A Sourcebook - Blum, Alexander S. (Sources 10: Max Planck Research Library for the History and Development of Knowledge, 2018)
This volume collects the earliest contributions to what is now known as quantum gravity research: the attempt to bring together quantum theory and the general theory of relativity. Covering the period from 1916-1950, it shows the beginnings of an unsolved problem that still remains as such today. The original sources are interspersed with historical essays, which together provide the first scholarly historical overview of quantum gravity in the first half of the twentieth Century. The combination of historical analysis and original sources make this a volume of interest to historians, philosophers, and physicists alike. - Edition Open Sources (EOS) pioneers a new paradigm in publishing, devoted to open access and high-quality peer review. This collaborative scholarly endeavor publishes academic editions of primary sources in the history of science in online, digital, and print formats. EOS publications present new editions of original sources with facsimile reproductions, in part also with translations, and with an introduction to the authors and the context in which they worked. The sources are typically historical books, manuscripts, documents or other material that is otherwise difficult to access. EOS a collaboration be-tween the University of Oklahoma Libraries, the Department for the History of Science of the University of Oklahoma and the Max Planck Institute for the History of Science in Berlin.